Análise da distribuição espacial da hanseníase no estado do Pará de 2012 a 2021 - GANZER, Geovanna Cristina de Sousa (2024)
Introduction: leprosy is an infectious, dermatoneurological disease characterized by slow and progressive evolution, caused by Mycobacterium Leprae, transmitted through the respiratory route, and has disabling potential. With the possibility of clinical epidemiological diagnosis, its treatment is offered free of charge through the Brazilian Unified Health System, and new cases of the disease must be mandatory registered through SINAN. Manifesting with heterogeneous characteristics in both population and space, this ailment exhibits widespread global dissemination, predominantly affecting underdeveloped countries like Brazil. At the subnational level, it is more consolidated, a situation observed in the state of Pará, which has shown high disease rates in recent decades. In this context, based on indicators of public health interest, the use of spatial mapping techniques aims to enhance the understanding of the epidemic and express characteristics of the disease's dynamics in the spatiotemporal context at the state level. Objectives: to demonstrate the territorial distribution of leprosy detection rates and their temporal evolution, as well as to identify and analyze regions of spatial autocorrelation of the disease in the state of Pará. Methods: this is an observational, ecological-analytical study that utilized secondary data from notifications of leprosy cases to SINAN, assessing 27.541 new cases of leprosy reported among the 144 municipalities and 6 mesoregions of Pará from 2012 to 2021. Average detection rates were calculated and analyzed by period. Additionally, mapped distribution, Moran's spatial autocorrelation test, and Local Indicators of Spatial Association (LISA) were performed to identify clusters with increased risk. Results: in the Pará scenario, the disease showed a percentage reduction in the cumulative average detection rate of 54.37% at the end of the series, and there was a change in the average classification from hyperendemicity to high endemicity. In spatial distribution, the disease presented itself heterogeneously in the state, with the majority of the territory experiencing high, very high, or hyperendemicity. The mesoregions of Southeast and Southwest Pará expressed a higher number of municipalities in hyperendemicity. In the spatial autocorrelation of the Local Moran's Index (li), zones of significance were identified with few variations over time. On average, 35.69% of the municipalities exhibited autocorrelation. Among these, clusters of High-High type were observed, indicating high circulation of M. Leprae in the south-central part of the state, while Baixo Amazonas exhibited Low-Low clusters, as did the northern coastal portion of the state. Comparatively, there was a contraction of High-High municipalities from the beginning of the period, but there was no expansion of Low-Low clusters. Conclusion: leprosy remains a health problem in the Pará scenario, with the average detection rate being high in most municipalities, especially in the Southeast and Southwest mesoregions of Pará. The spatial analysis elucidated the spatial dynamics of the disease over the years, as well as demonstrated the heterogeneity of its distribution and identified zones of persistence for M. Leprae circulation. This provides practical and scientific support for health interventions aimed at mitigating the advancement of the disease in Pará.